Potret Wanita ditengah Kemiskinan Modern - Abdul Muid (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2018)
Women are honorable and dignified human beings, as Allah greatly glorifies the dignity of women before Allah SWT. In the Qur'an Allah SWT. Mention one of the letters of the Qur'an is the letter "An-Nisa'". This proves that women are highly respected and upheld their dignity, status and dignity